2005
DOI: 10.1161/01.hyp.0000176588.51027.35
|View full text |Cite
|
Sign up to set email alerts
|

c-Src–Dependent Nongenomic Signaling Responses to Aldosterone Are Increased in Vascular Myocytes From Spontaneously Hypertensive Rats

Abstract: Abstract-Aldosterone plays an important role in the pathogenesis of hypertension. We previously demonstrated that nongenomic signaling by aldosterone in vascular smooth muscle cells occurs through c-Src-dependent pathways. Here we tested the hypothesis that upregulation of c-Src by aldosterone plays a role in increased mitogen-activated protein (MAP) kinase activation, [ 3 H]-proline incorporation, and NADPH-driven generation of reactive oxygen species, thereby inducing cell growth, collagen production, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 46 publications
(47 reference statements)
2
79
0
5
Order By: Relevance
“…4A) or the cSRC kinase inhibitor PP2 (100 nmol/liter, Fig. 4A), in accordance with the previously demonstrated EGFR and cSRC dependence of rapid MR signaling (9,15,39). Fig.…”
Section: Resultssupporting
confidence: 90%
“…4A) or the cSRC kinase inhibitor PP2 (100 nmol/liter, Fig. 4A), in accordance with the previously demonstrated EGFR and cSRC dependence of rapid MR signaling (9,15,39). Fig.…”
Section: Resultssupporting
confidence: 90%
“…The pathophysiological role of aldosterone in vascular hypertrophy and renal vascular diseases, as well as the potential application of Src or ATF1 blockage to antagonize the clinic vascular injury, warrants further study. that Src is the upstream of Nox1 in the VSMCs aldosterone response, which has already been shown by other groups [31,[33][34]. In this study, we revealed a novel pathway, Src-ATF1, in Nox1 activation and subsequently ROS generation in VSMCs following an aldosterone stimulus.…”
Section: Discussionsupporting
confidence: 83%
“…As described above, in addition to the MR-mediated genomic effects of aldosterone, non-genomic effects of aldosterone have also been described (7,8,53,54). Although it has been suggested that the non-genomic effects of aldosterone are mediated via MR (12,55), MR-independent mechanisms have also been reported to mediate the non-genomic effects of aldosterone (53,56).…”
Section: Effects Of Aldosterone/mr On Renal Hemodynamic Parameters Inmentioning
confidence: 96%
“…Aldosterone is classically known to bind to the cytosolic mineralocorticoid receptor (MR) in epithelial cells and aldosterone-bound MR translocates to the nucleus to promote protein synthesis. It has also been suggested that aldosterone, via rapid non-genomic pathways, regulates vasoconstriction (7) and c-Src activation in vascular smooth muscle cells (8). Although intrinsic glucocorticoids (cortisol in human and corticosterone in rodents) also show high affinity to the MR, aldosterone specially induces physiological responses through the MR by 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2)-dependent regulation.…”
Section: Introductionmentioning
confidence: 99%